NASIONALISME EKONOMI RUSIA PADA MASA PRESIDEN PUTIN (2000-2008) - -, Ardianto (Transformasi, 2014)
The problem in this research is how the policy of economic nationalism imposed on Russia by President Putin to replace the previous liberal economic system imposed by Yeltsin. With these problems, this research aims to determine the implementation of the policy of economic nationalism under President Putin is able to reinforce the Russian economy after crisis in the Yeltsin period. To achieve the research objectives, the research method use the type of descriptive study with data collection techniques through library (library research) are sourced from books, journals, documents and a valid website. While the authors analyze the data using qualitative analysis techniques with deductive writing techniques. From these results it can be seen that the policy of economic nationalism imposed by President Putin influenced by political conditions, economy and culture that form a strong Russia’s nationalist sentiment after the collapse of the Soviet Union. President Putin's policy of economic nationalism by the nationalization of strategic companies, decisive action against the oligarchs were considered detrimental to the national economy, as well as a series of deregulation of fiscal policy package proved able to restore the Russian economic crisis.. Keywords: putin, nationalism, economics, russia